Detection of The High Resoluiton in The Shallow Fault Reactive by The Geophysics Method, VLF-EM - Puguh Hiskiawan (Jurnal ILMU DASAR, 2009)
VLF-EM method is one of the geophysics methods used to examine rock structure below earth surface. The fault is an earth rock layering process that is usually filled with mineral or seeped with conductive fluid that cause conductivity changes. This fault influences a change in electromagnetic field parameter. This research applied interval variation measurement, to obtain high resolution conductivity. Karous-Hjelt filtering analysis methods was used to explain the response of VLF-EM method about fracture condition or fault reactive occurred in Renokenongo village, Sidoarjo. The result can identify a fault pattern which indicated a very significant reactive fault.